2021
DOI: 10.3390/foods10102366
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Responsible Food Packaging Perceptions on Naturalness and Healthiness Inferences, and Consumer Buying Intentions

Abstract: The research presented in this article examines the relationship between consumer perceptions that a food package is responsible (sustainable) and consumers’ intention to purchase the product that it contains. On the basis of the relevant literature, a conceptual model is proposed where this relationship is hypothesized to be mediated by two variables: the product’s perceived naturalness and healthiness. A first study was conducted with the objective of developing a scale with good psychometric properties to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…The relationship between sustainability and consumer attitudes and buying intentions for packages has been evidenced in the literature (D'Astous and Labrecque, 2021; Ketelsen et al. , 2020).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The relationship between sustainability and consumer attitudes and buying intentions for packages has been evidenced in the literature (D'Astous and Labrecque, 2021; Ketelsen et al. , 2020).…”
Section: Discussionmentioning
confidence: 96%
“…From a methodological perspective, such research analyses consumers' emotional responses usually through qualitative studies (Liao et al, 2015;Rundh, 2013;Silayoi and Speece, 2004), by using experimental designs based on focus groups and conjoint analysis (Chitturi et al, 2022;Elkhattat and Medhat, 2022;Eldesouky et al, 2016;Fernqvist et al, 2015;Kobayashi and Benassi, 2015;Schuch et al, 2018;Steenis et al, 2017). Quantitatively, analyses have been limited to the study of frequencies or correlations (D'Astous and Labrecque, 2021;O'Callaghan and Kerry, 2016) and researchers have used small samples and/or referred to a single country (Aday and Yener, 2015;O'Callaghan and Kerry, 2016;Schuch et al, 2018;Steenis et al, 2017). Furthermore, to our knowledge, the relationship between packaging attributes and intention to purchase experiential packages has not yet been sufficiently studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The next domain is that of the moderating effect of eco-friendly packaging. Previous research has contended that eco-friendly packaging functions as a clue for product appraisal [ 60 , 61 ]. Though it is not sufficient for appraising certain products precisely, packaging enables consumers to estimate their quality [ 20 , 61 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Not so much knowledge, but especially trust in the labels appeared to be important in this matter [ 6 ]. Investigating types of packaging, d’Astous and Labrecque found that a product package that is believed to be responsible (i.e., recyclable, reusable, compostable) triggers perceptions of the product being natural and healthy, which enhances consumers’ intention to buy the product [ 7 ]. Three manuscripts discuss product presentation styles.…”
mentioning
confidence: 99%